2014
DOI: 10.1111/saje.12056
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency Determinants and Capacity Issues in Angolan Insurance Companies

Abstract: This paper describes a variety of approaches used to assess the efficiency of a sample of major insurance companies in Angola between 2003 and 2012. Starting out with the bootstrapping technique, several data envelopment analysis (DEA) estimates were generated, allowing the use of confidence intervals and bias correction in central estimates to test for significant differences in efficiency levels and input‐decreasing/output‐increasing potentials. Previous studies have focused on the measurement and explanatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 54 publications
(62 reference statements)
1
15
0
Order By: Relevance
“…This differences in the production cycle and balance sheet structure makes it imperative to undertake this current empirical investigation to expand on the understanding of liquidity creation in insurance markets. Most importantly, evidence from emerging insurance markets appears virtually non‐existent, as microeconomic analysis of insurance markets in Africa have mostly been limited to efficiency (Barros et al ., ; Ansah‐Adu et al ., ; Barros and Wanke, ; Alhassan et al , ; Alhassan and Biekpe, ), profitability (Akotey et al, ; Asare et al ., ), competition (Alhassan and Biekpe, , 2018). The current study provides the first empirical estimate of liquidity de‐creation behaviour and explanatory factors in a developing insurance market.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This differences in the production cycle and balance sheet structure makes it imperative to undertake this current empirical investigation to expand on the understanding of liquidity creation in insurance markets. Most importantly, evidence from emerging insurance markets appears virtually non‐existent, as microeconomic analysis of insurance markets in Africa have mostly been limited to efficiency (Barros et al ., ; Ansah‐Adu et al ., ; Barros and Wanke, ; Alhassan et al , ; Alhassan and Biekpe, ), profitability (Akotey et al, ; Asare et al ., ), competition (Alhassan and Biekpe, , 2018). The current study provides the first empirical estimate of liquidity de‐creation behaviour and explanatory factors in a developing insurance market.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most of these studies have analyzed efficiency in single country as well as across countries in Africa. The studies by Chaffai and Ouertani (), Barros and Obijiaku (), Barros, Caporale, and Ibiwoye (), Ansah‐Adu et al (), Alhassan and Addison (), Barros, Dumbo, and Wanke (), Barros et al (), Wasseja and Mwenda (), Alhassan and Biekpe (), and Alhassan and Biekpe () among others have focused on individual African countries. For instance, Barros and Obijiaku () and Barros et al () studied the efficiency of insurance companies in Nigeria.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their two‐stage regression model confirmed that market share and firm size were positively related to efficiency whereas the ratio of equity to total invested asset was negatively related to cost efficiency in the Ghanaian insurance industry. Barros et al () described a variety of approaches used to assess the efficiency of a sample of major insurance companies in Angola between 2003 and 2012. Barros et al () combined neural networks with DEA results as part of an attempt to produce a model for insurance companies' performance with effective predictive ability.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The insurance literature in Africa has mostly focused on efficiency analysis (Barros, Ade Ibiwoye, & Managi, for Nigeria; Ansah‐Adu, Andoh, & Abor, for Ghana; Barros & Wanke, for Mozambique); Barros, Dumbo, & Wanke, for Angola and Alhassan & Biekpe, , for South Africa and financial performance (Akotey, Sackey, Amoah, & Manso, , Alhassan, Addisson, & Asamoah, , Asare, Alhassan, Asamoah, & Ntow‐Gyamfi, for Ghana) and competition (Alhassan & Biekpe, , for South Africa).…”
mentioning
confidence: 99%